A framework for determining product modularity levels. (October 2017) - Hvam, Lars; Herbert-Hansen, Zaza Nadja Lee; Haug, Anders; Kudsk, Anders; Mortensen, Niels Henrik
The application of modular products is seen as an important enabler for delivering customized products competitively. However, many companies struggle to find ways to implement modular products in a manner that suits their particular business. The literature includes examples of how modular products have been implemented in specific types of companies (mostly mass producers), but little guidance exists on how to identify the right level of modularity for other types of companies (such as engineer-to-order companies). In this article, we address this gap by suggesting a framework that categorizes the different types of modularity, where the categories fit different types of companies. More specifically, we introduce the Modularity Application Matrix – a conceptual tool that leads to a better understanding of partial modularization in relation to products. Through four case studies, its application in practice is illustrated. This article thereby contributes with new theoretical developments as well as a practical tool for practitioners in industries using partial modularization, such as the construction and building industry.